2006
DOI: 10.1051/0004-6361:20053602
|View full text |Cite
|
Sign up to set email alerts
|

Spectrophotometric properties of galaxies at intermediate redshifts (z ~ 0.2–1.0)

Abstract: We present the gas-phase oxygen abundance (O/H) for a sample of 131 star-forming galaxies at intermediate redshifts (0.2 < z < 1.0). The sample selection, the spectroscopic observations (mainly with VLT/FORS) and associated data reduction, the photometric properties, the emission-line measurements, and the spectral classification are fully described in a companion paper (Paper I). We use two methods to estimate the O/H abundance ratio: the "standard" R 23 method which is based on empirical calibrations, and th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
47
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 40 publications
(58 citation statements)
references
References 53 publications
10
47
1
Order By: Relevance
“…On the contrary, Carollo & Lilly (2001), from emission-line ratios of 15 galaxies in a range of 0.5 < z < 1, found that their metallicities appear to be remarkably similar to those of local galaxies selected with the same criteria. A similar result, consistent with no significant evolution, was found for the luminosity-metallicity relation by Lamareille et al (2006), comparing 131 intermediate redshift star-forming galaxies (0.2 < z < 1, split in 0.2 redshift bins). However, a recent study of Lamareille et al (2009), focussed on the evolution of the M − Z relation up to z ∼ 0.9, suggesting that the M − Z relation is flatter at higher redshifts.…”
Section: Introductionsupporting
confidence: 87%
See 1 more Smart Citation
“…On the contrary, Carollo & Lilly (2001), from emission-line ratios of 15 galaxies in a range of 0.5 < z < 1, found that their metallicities appear to be remarkably similar to those of local galaxies selected with the same criteria. A similar result, consistent with no significant evolution, was found for the luminosity-metallicity relation by Lamareille et al (2006), comparing 131 intermediate redshift star-forming galaxies (0.2 < z < 1, split in 0.2 redshift bins). However, a recent study of Lamareille et al (2009), focussed on the evolution of the M − Z relation up to z ∼ 0.9, suggesting that the M − Z relation is flatter at higher redshifts.…”
Section: Introductionsupporting
confidence: 87%
“…Since then, as luminosities are easier to estimate than masses, many studies have focussed on the L − Z relation (e.g., Skillman et al 1989;Brodie & Huchra 1991;Zaritsky et al 1994;Garnett et al 1997;Lamareille et al 2004Lamareille et al , 2006Maier et al 2004), which correlates the absolute magnitude of galaxies with metallicity, being the more metal rich, the more luminous. The M − Z and L − Z relations have been studied at both, low and high redshift (e.g.…”
Section: Effect Of the Mass And Luminosity-metallicity Relationsmentioning
confidence: 99%
“…However, the adopted calibration of R 23 is not based on galaxies with direct metallicities but on grids of photoionization models, which may produce a systematic bias. To overcome these differences, we follow Pérez- Montero et al (2013) and convert the metallicities derived from R 23 to those derived from N2 using the linear relations described in Lamareille et al (2006b), which are based on models of Charlot & Longhetti (2001). This way, the adopted estimators find metallicities that are broadly consistent, within the uncertainties, with each other.…”
Section: Metallicity From Strong-line Methodsmentioning
confidence: 99%
“…Since then, as luminosities are easier to estimate than masses, many studies have focused on the L − Z relation (e.g., Skillman et al 1989;Brodie & Huchra 1991;Zaritsky et al 1994;Garnett et al 1997;Lamareille et al 2004Lamareille et al , 2006Maier et al 2004), which correlates the absolute magnitude of galaxies with metallicity, the more metal rich being more luminous. The M − Z and L − Z relations have been studied at both low and high redshift (e.g.…”
Section: Effect Of the Mass And Luminosity-metallicity Relationsmentioning
confidence: 99%